Development of Universitas Padjadjaran as Educational Tourism Destination - Maulana, Muhammad Iqbal; Putra, Rifki Rahmanda; Permadi, Raden Willy Ananta (Journal of Tourism Education, 2021)
Discussion about educational tourism, not only about student exchange programs or study abroad activities. However, the packaging of education-based tourism activities in a destination is also included in the terminology of educational tourism. This study aims to identify the potential of educational tourist attraction and develop alternative educational tourism programs at UNPAD, Jatinangor. This study uses a method with a qualitative approach, with primary data collection techniques through field surveys and in-depth interviews with the management of UNPAD. Secondary data obtained through literature studies related to previous research and local government policy documents. The collected data is processed using descriptive analysis techniques. The study found that there is a potential educational tourism attraction in the form of 16 faculties which are divided into concentrations of natural and social sciences. Each faculty is supported by adequate amenities and accessibility. The educational tourism development program at UNPAD, Jatinangor is divided into four main programs, including educational tourist attractions development, human resources development, activities development and marketing.